The Derivational Field of the Noun kaimas (‘village’) - Vaskelienė, Jolanta (Acta humanitarica academiae Saulensis, 2019)
The majority of words of the Lithuanian lexicon are derivatives, not base words. In the Lithuanian language, words are derived not only from the base words, but from derivatives as well. Thus, in Lithuanian, a derivational field around a word is often formed. The article analyses the derivational field of the noun kaimas (‘village’). Having analyzed 108 derivatives with the root kaim found in Dictionary of the Lithuanian Language (LKŽe), Digital Supplement Card File of Dictionary of the Lithuanian Language (PK), Dictionary of Modern Lithuanian (DLKT), list of Dictionary of Standard Lithuanian (BŽa), the Database of Lithuanian Neologisms (NŽ) and The Corpus of the Contemporary Lithuanian Language (DLKT), the following conclusions were drawn:1. The greater part of the derivational field of the noun kaimas comprises the derivatives of level 1 (62, or 57 percent of all derivatives); the number of level 2 derivatives is smaller (40, or 37 percent of all derivatives), the number of level 3 derivatives is the smallest (6, or 6 percent of all derivatives).2. In the derivational field nouns dominate (86 derivatives were found): they make up 80 percent of all derivatives. The field has significantly fewer adjectives (13, or 12 percent of all derivatives), very few verbs (6, or 5 percent) and adverbs (3, or 3 percent). Some of derived nouns are abstract nouns, but most often they refer to a place and a person.3. In addition to regular cognite derivatives recorded in dictionaries, the derivational field contains neologisms: they make up 11 percent of all derivatives. Most of the neologisms are potential derivatives: they are quite common, formed by regular types of word formation, and their meaning is easily understood from the context. Some of the neologisms can be considered to be uncommon derivatives.4. Some of the derivatives with the same root are in free variation or are synonyms (16 sequences of derivational variants (DV) and 9 sequences of derivational synonyms (DS) were formed and analysed). Some DS have a high degree of synonymy, have identical or very similar meanings, are used in similar lexical environments, and can be substituted without much restriction. However, the DLKT data showed that usually there is a difference in the frequency of use of DS and DV sequence members: there is a tendency in the current Lithuanian language to use only certain members of synonym (and variant) sequence. Some derivatives (usually not included in DLKŽ and BŽa) are used very rarely or are not used in the current Lithuanian language at all.
Keywords: derivative; compound; derivational field; derivational synonyms; derivational variants